2018
DOI: 10.3390/ijerph15112546
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Satisfaction of Hospital Physicians: A Systematic Review on European Data

Abstract: Background: Physician satisfaction is a multidimensional concept related to many factors. Despite the wide range of research regarding factors affecting physician satisfaction in different European countries, there is a lack of literature reviews analyzing and summarizing current evidence. The aim of the article is to synthetize the literature studying the factors associated with physician satisfaction. Methods: We searched: MEDLINE, Embase, PsycINFO, CINAHL and the Cochrane Library from January 2000 to Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…However, in a separate analysis we found that those making >AU$150 000 per year were significantly less satisfied than those in the median income group, which indicates that there may be a ceiling effect to income and satisfaction. There is very little other evidence in this area for specialist trainees although a large 2002 study carried out in UK hospital physicians found that only the middle‐income band (GBP35 000‐49 999) reported significantly higher levels of satisfaction in comparison with the lowest (GBP20 000) and otherwise found no clear effect of income . By contrast, in general practice, the link between low remuneration and poor job satisfaction has been well established in studies from a multiplicity of countries and settings, with most of these studies emphasising dissatisfaction when there is a discrepancy between long hours and remuneration .…”
Section: Discussionmentioning
confidence: 99%
“…However, in a separate analysis we found that those making >AU$150 000 per year were significantly less satisfied than those in the median income group, which indicates that there may be a ceiling effect to income and satisfaction. There is very little other evidence in this area for specialist trainees although a large 2002 study carried out in UK hospital physicians found that only the middle‐income band (GBP35 000‐49 999) reported significantly higher levels of satisfaction in comparison with the lowest (GBP20 000) and otherwise found no clear effect of income . By contrast, in general practice, the link between low remuneration and poor job satisfaction has been well established in studies from a multiplicity of countries and settings, with most of these studies emphasising dissatisfaction when there is a discrepancy between long hours and remuneration .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in numerous countries have conducted studies focused on satisfaction [4,8,9] as well as stress and burnout among physicians working in university hospitals [10][11][12]. Physician satisfaction is a complex and multidimensional concept which can be affected by personal and external factors [13,14]. Physicians' satisfaction has significant effects on their productivity, their work ability, and the quality of patient care, as well as their intentions to leave the job or their intent to continue practicing medicine [15][16][17].In 2018 in Poland, there were 36 university hospitals owned and operated by 13 public medical universities.…”
mentioning
confidence: 99%
“…A lack of validated and reliable psychometric instruments limit study results, as well as their comparability [32]. Also, researchers call for international collaborative studies to better understand the satisfaction of physicians and associated factors [2,33]. Similarly, multifaceted measures of physicians' satisfaction are needed to understand challenges and define effective actions to improve the wellness of physicians [2].…”
Section: Discussionmentioning
confidence: 99%